FREQUENCY, URINALYSIS AND SUSCEPTIBILITY PROFILE OF PATHOGENS CAUSING URINARY TRACT INFECTIONS IN ENUGU STATE, SOUTHEAST NIGERIA - Dibua, Uju M.E.; Onyemerela, Ifeoma S.; Nweze, Emeka I. (Revista do Instituto de Medicina Tropical de São Paulo, 2014)
Objective: This study was designed to determine the frequency and causative agent(s) of urinary tract infections (UTIs) in individuals with symptoms of urinary tract infections in Enugu State of Southeast Nigeria, and to determine the antibiotic susceptibility pattern of microbial agents isolated from urine culture. Methods: The study involved 211 individuals (149 females and 62 males) clinically suspected for UTI. Urine samples were collected by the mid-stream ‘clean catch' method and tested using standard procedures. Antibiotic susceptibility of the isolated pathogens was tested using the Kirby-Bauer technique according to the Clinical and Laboratory Standards Institute (CLSI) guidelines. Results: Microscopy of centrifuged urine samples showed 16 patients had pyuria while 54 had pus cells. Calcium oxalate crystals were found in 14 samples. Urinalysis performed with urine samples showed 17 had protein; seven were nitrite positive and three had moderate to high glucose concentration. Fifty-four urine samples (36.2%) from females and 12 (19.4%) from males showed significant growth upon culture. Gram stain and biochemical tests identified nine different organisms with Escherichia coli as the most common isolated species. Forty three randomly selected strains were further tested for their susceptibility against a panel of antibiotics. Thirty isolates (81.08%) were resistant to four or more antibiotics with the highest resistance shown by E. coli (76.67%). All the Gram- negative isolates were resistant to Ampicilox, Cefuroxime and Amoxicillin. Conclusion: Urinary tract infections were found more in females in the area under study. As found in other studies, E. coli was the most predominant isolate, although other organisms seem to be on the increase.